Dyslexie : metody reedukace, výuky a hodnocení - Jucovičová, Drahomíra, 1962-; Žáčková, Hana, 1960- (PaedDr. Drahomíra Jucovičová - nakladatelství D + H, 2020)
Metodika, výuka a hodnocení pro práci s dyslektiky.